Evaluation of Cloud Computing Implementation in Industry 4.0 at Cloud Infrastructure PT X - Haqi, Muti Pertama; Adhariani, Desi (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
The research aims to analyse impact of digital transformation at PT X as cloud infrastructure provider. Digital transformation has been increased globally because they have their internet infrastructure well established, meanwhile in Indonesia still needs to develop which has 3% annually of development headway. The usage of internet increases every year in every activity so that it supports the digital transformation. This research conduct to analyse by using PESTEL analysis and TOE framework at PT X as cloud infrastructure provider. The issues are found, at first cloud is used as a massive storage for certain activity such as for office needs. However, currently activities have been changed to be daily activities in cyber world so that generates big data. The next issue, cloud has been considered as environmental friendly product because it reduces usage of resources meanwhile for data centre activity consumes massive amount electricity so that contributes to create carbon emission. Digital transformation forms from various kind of cyber activities, this could be as potential market for PT X to elaborate their business. Unfortunately PT X profitability has fluctuated in this 5 years when the demands of technology increase. This research is a qualitative method with case study approach and the instrument of research is by doing interview. Data were gained as primary and secondary data. Current research is using PESTEL analysis and TOE framework. This explains external factors which identified by PESTEL analysis could affect business strategy and TOE framework could determine kinds of innovation based on its character of technology so that these analysis could bring the decision of company strategy.